Kontribusi Santripreneurship Sebagai Potensi Kemandirian Ekonomi Umat di Yogyakarta - Isti, Istiqomah Faiz; Fauzan, Fauzan (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2022)
This study aims to determine the role of Islamic boarding schools in promoting entrepreneurship towards the economic independence of the people in the D.I Yogyakarta region. The research method used is literature review by collecting data and information related to Islamic boarding schools with economic independence and santripreneurship through supporting data sourced from national research journals, newspapers, websites, direct interviews with research objects, and social media. The results of the study show that there is support from the government and non-governmental organizations in mobilizing entrepreneurial pesantren, various pesantren have great potential in promoting entrepreneurship with various activities, the role of santri becomes capital in fulfilling the entrepreneurial spirit of pesantren, and pesantren in the DI Yogyakarta region make a positive and empowered contribution for economic independence. people.